2020
DOI: 10.2196/21436
|View full text |Cite
|
Sign up to set email alerts
|

A Remote Nutritional Intervention to Change the Dietary Habits of Patients Undergoing Ablation of Atrial Fibrillation: Randomized Controlled Trial

Abstract: Background The Prevention With Mediterranean Diet (PREDIMED) trial supported the effectiveness of a nutritional intervention conducted by a dietitian to prevent cardiovascular disease. However, the effect of a remote intervention to follow the Mediterranean diet has been less explored. Objective This study aims to assess the effectiveness of a remotely provided Mediterranean diet–based nutritional intervention in obtaining favorable dietary changes in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Five pooled studies (n = 927 participants) 28,33,34,41,54 found no significant effect of digital health intervention on protein intake (MD = −0.13 grams/day; 95% CI = −1.42 to 1.16; p = 0.84; I 2 = 12%). There were three studies 34,35,44 that reported varying measures of protein intake (e.g., protein component of diet quality index score and adherence to protein intake).…”
Section: Protein Intakementioning
confidence: 99%
See 4 more Smart Citations
“…Five pooled studies (n = 927 participants) 28,33,34,41,54 found no significant effect of digital health intervention on protein intake (MD = −0.13 grams/day; 95% CI = −1.42 to 1.16; p = 0.84; I 2 = 12%). There were three studies 34,35,44 that reported varying measures of protein intake (e.g., protein component of diet quality index score and adherence to protein intake).…”
Section: Protein Intakementioning
confidence: 99%
“…The characteristics and main findings of the studies are provided in Table 1. Studies were conducted within hospitals (n = 20 studies), [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] community health care (n = 16 studies) [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] or a combination of these settings (n = 3). [61][62][63] The majority of studies were randomised control trials (n = 37 studies) with either two (n = 31 studies), [25][26][27][28][29][30][31][33][34]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations